2022
DOI: 10.1186/s12891-022-05003-7
|View full text |Cite
|
Sign up to set email alerts
|

An anti-inflammatory diet intervention for knee osteoarthritis: a feasibility study

Abstract: Background Knee osteoarthritis has an inflammatory component that is linked to pain and joint pathology, yet common non-surgical and non-pharmacological interventions (e.g., exercise, calorie restricting diets) do not typically target inflammation. We aimed to evaluate the feasibility of a telehealth delivered anti-inflammatory diet intervention for knee osteoarthritis. Methods This 9-week single-arm feasibility study recruited participants aged 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Visual Analogue Scale (VAS): a scale used to measure pain. It consists of a horizontal or a vertical line that represents the pain intensity with a score from 0 to 10, where the number 0 is synonymous with “no pain” and 10 is synonymous with “very intense pain/worst pain imaginable” [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual Analogue Scale (VAS): a scale used to measure pain. It consists of a horizontal or a vertical line that represents the pain intensity with a score from 0 to 10, where the number 0 is synonymous with “no pain” and 10 is synonymous with “very intense pain/worst pain imaginable” [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerical Pain Scale (NPRS): a one-dimensional tool for measuring pain in adults, consisting of 11 items. It is a version of the VAS scale that has scores from 0 to 10, with 0 being synonymous with “no pain” and 10 being “the most intense pain imaginable” [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given inherent differences in the FEAST RCT (eg, Australian Dietary Guideline control group, not specifically targeting overweight participants, inclusion of both women and men), we used the lower bound 95% CI to provide a conservative estimate of the anticipated effect size (0.5). This estimated effect size is also a conservative estimate based on our single-arm anti-inflammatory diet pilot trial, which had an effect size of 0.68 28. Recruiting 128 participants (equally distributed between two arms) would yield 80% power to observe such an effect or larger at a two-tailed type I error of 0.05.…”
Section: Data Managementmentioning
confidence: 93%
“…Anti-inflammatory diets have garnered much interest in recent years due to their effectiveness in alleviating symptoms and improving biomarkers for a variety of chronic diseases, including diabetes,18 cardiovascular disease,24 epilepsy25 and rheumatoid arthritis 26. Small studies investigating anti-inflammatory diets for knee OA have demonstrated feasibility and effectiveness in reducing symptoms and inflammation over 12–16 weeks 15 27 28. To date, no fully powered randomised controlled trial (RCT) has evaluated the effectiveness of an anti-inflammatory diet in knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, anti-inflammatory diets include the consumption of unrefined and minimally processed foods, nutrients including fiber, mono- and poly unsaturated fatty acids, lean protein sources such as chicken, and various spices, and reducing the consumption of red meat, high-fat dairy foods, and saturated and trans fats that have notably been shown to diminish inflammation [ 89 , 90 ]. The effect of an anti-inflammatory diet on weight loss has been reported many times.…”
Section: Influence Of Anti-inflammatory Diet On Gut Microbiota Insuli...mentioning
confidence: 99%